Pengembangan Media Smart Box pada Pembelajaran IPAS Siswa - Agustin, Nadila; Prananosa, Ahmad Gawdy; Krisnawati, Yuni (IJOCE: Indonesia Journal of Civic Education, 2025)
This research aims to develop a Smart Box media in the science learning of fourth-grade students of SD Negeri 37 Lubuklinggau that is valid, practical and effective. The research method used is Research and Development using the ADDIE model. The results showed that the validation analysis of Smart Box media using Aiken's V obtained a value from the language validator of 0.98 with a high category, a media validator of 0.82 with a high category and a material validator of 0.89 with a high category. The analysis of the assessment of the practicality sheet of teachers and students met the practical criteria with a score of 97.67% with a very practical category, then the analysis of the effectiveness assessment obtained an average N-Gain score of 0.68 with a moderate category. The conclusion of this study is the development of Smart Box media in science learning of fourth-grade students of SD Negeri 37 Lubuklinggau is proven to be valid, practical and effective so that it is suitable for use in science learning of fourth-grade students of SD Negeri 37 Lubuklinggau.   Keywords: Development; Elementary school, IPAS, Smart Box.